Interactive effects of prenatal adversity and COVID-19 hardship on youth psychological distress: a longitudinal study - Wang, Yifan; Wang, Xinni; Voyer, Chloé; Brunet, Alain; Ateba, François Freddy; Wazana, Ashley; Laplante, David P. (Frontiers in Child and Adolescent Psychiatry, 2025)
IntroductionThe COVID-19 pandemic resulted in severe loss of life and increased anxiety as well as fear worldwide. This study explored whether pre-pandemic exposure to varying levels of perinatal maternal adversity coupled with pandemic-related experiences are related to youth distress levels.MethodsData from 119 youth (aged 9–17) and their mothers were analyzed to assess the interactive effects of perinatal maternal adversity and pandemic-related objective hardship on youth psychological distress.ResultsYouth-reported hardship models consistently explained more variance in their psychological distress. Youth-reported hardship, specifically daily life changes, predicted psychological distress, including PTSD symptoms and peritraumatic experiences during the pandemic.DiscussionYouths exposed to high perinatal maternal socio-environmental adversity demonstrated resilience when faced with pandemic disruptions, suggesting that alignment between early adversity and later stress can mitigate distress during crises.